2005
DOI: 10.1590/s0100-879x2005000500014
|View full text |Cite
|
Sign up to set email alerts
|

Profile of thyroid hormones in breast cancer patients

Abstract: Estrogen involvement in breast cancer has been established; however, the association between breast cancer and thyroid diseases is controversial. Estrogen-like effects of thyroid hormone on breast cancer cell growth in culture have been reported. The objective of the present study was to determine the profile of thyroid hormones in breast cancer patients. Serum aliquots from 26 patients with breast cancer ranging in age from 30 to 85 years and age-matched normal controls (N = 22) were analyzed for free triiodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 17 publications
5
59
1
3
Order By: Relevance
“…Epidemiologic studies have shown a possible association between thyroid dysfunction and BC. Postmenopausal BC patients have been reported to have a significant increase in THs, suggesting that an imbalance between estradiol (E2) and T3 fosters the development of BC [44][45][46] . Conversely, hyperthyroidism has been associated with a reduction in the incidence of BC [47] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Epidemiologic studies have shown a possible association between thyroid dysfunction and BC. Postmenopausal BC patients have been reported to have a significant increase in THs, suggesting that an imbalance between estradiol (E2) and T3 fosters the development of BC [44][45][46] . Conversely, hyperthyroidism has been associated with a reduction in the incidence of BC [47] .…”
Section: Resultsmentioning
confidence: 99%
“…As shown by Tosovic et al [56] , high levels of T3 in postmenopausal women positively correlate with the risk of BC in a doseresponse manner. In the case of hyperthyroidism, this correlation was found in postmenopausal women but not in premenopausal woman who had BC [44] . These postmenopausal women with BC had a significant increase in their thyroid/estradiol ratio, suggesting that an imbalance between E2 and T3 fosters the development of BC [44] .…”
Section: Cancermentioning
confidence: 93%
See 2 more Smart Citations
“…Full--text ar+cles assessed for eligibility (n =21) Figure.1) (Turken et al, 2003;Cengiz et al, 2004;Kuijpens et al, 2005;Saraiva et al, 2005;Giustarini et al, 2006;Ditsch et al, 2010;Ali et al, 2011;Szychta et al, 2013) . Tables 1 and 2 show the characteristics and data of all 8 studies included in our analysis.…”
Section: Iden0fica0onmentioning
confidence: 99%